CONTROLLING THE SPEED OF ROLLING CUTS IN CONDITIONS OF REDUCTION OF BRAKE POWER OF CAR RETARDERS - Kozachenko, D. M.; Bobrovskyi, V. I.; Grevtsov, C. V.; Berezovyi, M. I. (Science and Transport Progress, 2021)
Purpose. The study aims to develop the requirements for organization of the marshalling process in the conditions when the power of retarder positions is less than the nominal one. Methodology. The research is carried out using the train traffic safety theory and mathematical modelling of hump processes. Findings. The current technical standard documents regulating the operational performance of humps do not contain direct instructions on how to proceed in the event of brake power loss by car retarders, thus creating threats to the traffic safety. This problem is quite acute for the Ukrainian railways in connection with a chronic shortage of funds for the repair and renewal of technical equipment, including the humps. At the same time, a significant drop in the volume of work leads to the fact that the hump required processing capacity can be provided in case of partial failure of retarders as well. Herewith the most important task is to ensure the breaking-up safety in conditions of parametric failures of retarders. The analysis of dangerous situations, the occurrence of which is possible at humps, as well as the modelling of cut rolling, allowed establishing the connection between the value of retarder tire pressing force on the car wheels and the breaking-up modes, providing the safety of marshalling process. The paper sets the application areas of such measures as the breaking-up speed reduction, breaking-up termination, the use of additional braking by block hangers. Originality. The originality of the work lies in the fact that it first obtained the complex of dependencies that determine the performance requirements for the power of hump retarders and allow the staff to enter the appropriate limits for breaking-up modes to ensure the marshalling process safety. Practical value. The results of the research can be used to supplement the «Instruction on the maintenance of facilities of mechanized and automated humps» in order to determine the limits of breaking-up modes when detecting the reduction of retarder power below the nominal one.